2019
DOI: 10.1039/c9fo00994a
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of tenuifolin isolated from Polygala tenuifolia Willd roots on neuronal apoptosis and learning and memory deficits in mice with Alzheimer's disease

Abstract: The roots of Polygala tenuifolia Willd have a long history of being used as a traditional Chinese medicine for the treatment of insomnia, forgetfulness, sorrow and depression. This research show the special function in Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…69,70 The chemical composition of PT is relatively complicated but mainly includes: (1) a variety of saponins that are isolated from the roots of Polygala saponin, and the identified structures are Polygala saponin A, B, E, F, and G (structurally, the basic mother nucleus of Polygala saponin is oleanolic acid, a type of pentacyclic triterpene); (2) oral ketone, which exists only in the form of derivatives in plants (most of the substituents are hydroxyl and methoxy forms, and a few are methylenedioxy); (3) a large number of sugar ester components (its parent core structure has four types [A, B, C, and D], and there are 12 types of substituents); (4) alkaloids, namely R1 R2 N9formylhalman; and (5) other ingredients, such aspolygalol, 3,4,5-trimethoxycinnamic acid, stigmasterol, a-spinasterol glucoside, and rich fatty oils and resins. 71,72 Pharmacological research found that PT has protective effects on neuronal apoptosis and learning and memory impairment in mice models of AD; 73 improves behavioral abnormalities in mice with depression 74 and improves hippocampal-dependent learning and memory. 75 One of the main active ingredients of PT is 3,4,5-trimethoxycinnamic acid (TMCA), 76 which has anticonvulsant, 77 antitumor, 78 antiepileptic, 79 and anti-stress 80 properties and improves cognitive function.…”
Section: Polygala Tenuifolia Willdmentioning
confidence: 99%
“…69,70 The chemical composition of PT is relatively complicated but mainly includes: (1) a variety of saponins that are isolated from the roots of Polygala saponin, and the identified structures are Polygala saponin A, B, E, F, and G (structurally, the basic mother nucleus of Polygala saponin is oleanolic acid, a type of pentacyclic triterpene); (2) oral ketone, which exists only in the form of derivatives in plants (most of the substituents are hydroxyl and methoxy forms, and a few are methylenedioxy); (3) a large number of sugar ester components (its parent core structure has four types [A, B, C, and D], and there are 12 types of substituents); (4) alkaloids, namely R1 R2 N9formylhalman; and (5) other ingredients, such aspolygalol, 3,4,5-trimethoxycinnamic acid, stigmasterol, a-spinasterol glucoside, and rich fatty oils and resins. 71,72 Pharmacological research found that PT has protective effects on neuronal apoptosis and learning and memory impairment in mice models of AD; 73 improves behavioral abnormalities in mice with depression 74 and improves hippocampal-dependent learning and memory. 75 One of the main active ingredients of PT is 3,4,5-trimethoxycinnamic acid (TMCA), 76 which has anticonvulsant, 77 antitumor, 78 antiepileptic, 79 and anti-stress 80 properties and improves cognitive function.…”
Section: Polygala Tenuifolia Willdmentioning
confidence: 99%
“…The Shen Yuan prescription (SY) comprises Panax ginseng (GT) and Polygala tenuifolia (YT), which are traditional Chinese herbal medicines with a wide range of neurotrophic and neuroprotective effects and that are widely used for treating several neurologic disorders, such as depression (Bo et al, 2012; Wang et al, 2019). In one of our earlier studies, we demonstrated the superior efficacy of the SY prescription as an antidepressant compared with GT or YT alone using tail suspension and forced swim tests (Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Polygala Tenuifolia (PT), also known as Yuan Zhi in Chinese, is a famous traditional Chinese medicine which has been widely applied to treat central nervous system diseases including dementia and neurasthenia [ 15 ]. Numerous pharmacological studies have demonstrated that PT possessed multiple neuroprotective effects associated with AD, such as anti-apoptosis [ 16 ], anti-neuroinflammation [ 17 ], enhancing neurotrophy [ 18 ] and anti-neurotoxicity induced by β-amyloid (Aβ) [ 19 ]. Moreover, it has been reported that PT extract promoted NSCs proliferation in vitro and enlarged the amount of NSCs in hippocampal CA1 regions in adult rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%